2021
DOI: 10.1002/chem.202004954
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Anticancer Activity of Furoylthiourea‐Based RuII–Arene Complexes and Their Mechanism of Action

Abstract: Fourteen new RuII–arene (p‐cymene/benzene) complexes (C1–C14) have been synthesized by varying the N‐terminal substituent in the furoylthiourea ligand and satisfactorily characterized by using analytical and spectroscopic techniques. Electrostatic potential maps predicted that the electronic effect of the substituents was mostly localized, with some influence seen on the labile chloride ligands. The structure–activity relationships of the Ru–p‐cymene and Ru–benzene complexes showed opposite trends. All the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 69 publications
3
32
0
Order By: Relevance
“…The micro-morphological observation study concluded that SeNPs have selectively influenced the cellular damage in cancer cells. Thus, SeNPs were found to be biocompatible toward normal cells ( Swaminathan et al, 2019 , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The micro-morphological observation study concluded that SeNPs have selectively influenced the cellular damage in cancer cells. Thus, SeNPs were found to be biocompatible toward normal cells ( Swaminathan et al, 2019 , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxic effects of SeNPs on both normal and cancerous cell populations were measured using the MTT assay, which was determined by the cellular proliferation rate and cell viability (Swaminathan et al, 2019(Swaminathan et al, , 2021Kota et al, 2021). The methodology is provided in the Supplementary Data [(10) Cell viability and micro-morphology assessment].…”
Section: Cell Viability and Micro-morphology Assessmentmentioning
confidence: 99%
“…Rhodamine 123, a green fluorescent cationic dye, has been used to measure the mitochondrial membrane potential. It stains the viable cells of mitochondria in the membrane potential-dependent fashion . The concentration of the dye has been noticed to investigate the mitochondrial functions of the treated and untreated cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The basis set used for the analyses was LANL2DZ with B3LYP functional. [27,28] The optimized structures and calculated bond lengths are shown in Figure 2 and Table 1, respectively. The bond lengths were in accordance with those reported for similar Ru(II)-DMSO complexes.…”
Section: Optimization Of the Structures And Calculation Of Electrophi...mentioning
confidence: 99%